The Effect of Regional Government Expenditures on Regional Development Inequality in Eastern Indonesia, 2015-2020 - Viqra Ramadanti; Agussalim Agussalim; Sultan Suhab (Jambura Equilibrium Journal, 2023)
The existence of differences in resources and processes in the implementation of development in a region causes the ability of each region to encourage the development process also to be different, which causes problems of development inequality between regions. Therefore, an analysis of regional development disparities needs to be carried out. This study aims to analyze the effect of local government spending, the Human Development Index (HDI), and economic growth on regional development inequality in Eastern Indonesia in 2015-2020. This research approach uses a quantitative approach. The data type used is panel data, 12 Provinces in Eastern Indonesia for six years (2015-2020). The analysis tool uses panel data regression with a Fixed Effect Model approach. The results indicate that the variables of government spending on education, health, infrastructure, and human development index directly affect regional development inequality. Meanwhile, the economic growth variable does not affect regional development inequality.